Postdoctoral life in Japan / Dr. Nurfarhana Ferdaos - Ferdaos, Nurfarhana (Faculty of Pharmacy, 2023)
In April 2023, I started my postdoctoral research at the Center for Induced Pluripotent Stem Cell and Research Applications (CiRA), Kyoto University. Established by the 2012 Nobel Laureate, Professor Shinya Yamanaka, this research institute is dedicated to fundamental and clinical research on his novel finding, induced pluripotent stem (iPS) cells. I am very grateful for the opportunity given by Assoc. Prof. Knut Woltjen to be part of his group, which focuses on developing genome and epigenome editing technologies for disease modelling using iPS cells. My current research is part of a collaborative work between prestigious research and academic institutions in the UK and the US, funded by a biotech company.